2018
DOI: 10.3390/nu10060689
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Supplementation Alleviates Puromycin Aminonucleoside Damage by Modulating Endoplasmic Reticulum Stress and Mitochondrial-Related Apoptosis in Rat Kidney

Abstract: Taurine (TAU) is a sulfur-containing beta amino acid that is not involved in protein composition and anabolism, conditionally essential in mammals provided through diet. Growing evidence supports a protective role of TAU supply in osmoregulation, calcium flux, and reduction of inflammation and oxidant damage in renal diseases like diabetes. Endoplasmic reticulum (ER) stress, due to abnormal proteostasis, is a contributor to nephrotic syndrome and related renal damage. Here, we investigated the effect of dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Taurine is one of abundant free amino acids in mammals' tissues and implicated in oxidative damage, endoplasmic reticulum stress, and apoptosis (Timbrell et al, 1995;Jong et al, 2017). Hence, taurine has been reported to protect against kidney injure (Adedara et al, 2017;Stacchiotti et al, 2018;Adedara et al, 2019). In the present study, db/db mice had a significantly lower level of renal taurine than age-matched wt mice, but its level was significantly increased after bFGF treatment.…”
mentioning
confidence: 40%
“…Taurine is one of abundant free amino acids in mammals' tissues and implicated in oxidative damage, endoplasmic reticulum stress, and apoptosis (Timbrell et al, 1995;Jong et al, 2017). Hence, taurine has been reported to protect against kidney injure (Adedara et al, 2017;Stacchiotti et al, 2018;Adedara et al, 2019). In the present study, db/db mice had a significantly lower level of renal taurine than age-matched wt mice, but its level was significantly increased after bFGF treatment.…”
mentioning
confidence: 40%
“…It also has magnesium ion-dependent ATPase activity. The unfolded polypeptide chains can be combined to prevent protein accumulation, help protein folding, stretching, assembly and transport, thereby preventing the secretion of misfolded proteins (20)(21)(22). Therefore, GRP94 is also an important marker of ERS and acts a part in lipid and protein metabolism.…”
Section: Results Of Correlation Analysis Between Rhi and Clinical Ind...mentioning
confidence: 99%
“…To ensure proper organ development, individuals need extra taurine from the daily diet (Jung & Choi, 2019). Previous studies have reported that several diseases, including diabetes, heart failure, muscle and inflammatory diseases, and metabolic diseases, are associated with taurine deficiency (Schaffer & Kim, 2018; Stacchiotti et al, 2018). However, whether taurine deficiency also occurs during intestinal aging remains unknown.…”
Section: Resultsmentioning
confidence: 99%